Genome-wide identification and characterization of ALOG domain genes in Rosa - Chen, Feng; Lv, Bo; Guo, Jiaqi; Song, Jurong; Guo, Cong; Yang, Jie; Lin, Jianguo; Yang, Yuanyuan; Xiang, Fayun (Frontiers in Plant Science, 2025)
IntroductionALOG genes encode transcription factors that control essential growth and developmental processes in various plant species. The ALOG protein domain, which is highly conserved among land plants, exhibits distinct evolutionary patterns in different plant lineages, suggesting its importance in plant adaptation and evolution. Rosa (roses), a genus of flowering plants with significant horticultural value, exhibits key traits such as floral organ differentiation and inflorescence architecture diversification. Emerging evidence suggests that ALOG genes not only modulate organogenesis but may also drive evolutionary innovations in floral organ morphology and inflorescence complexity.MethodsWe systematically identified ALOG genes in four Rosa genomes (R. chinensis, R. multiflora, R. rugosa, and R. wichurana), reconstructed their phylogenetic relationships, and cloned ALOG homologs from R. chinensis.ResultsThrough integrated bioinformatic analyses including chromosomal localization, protein motif characterization, promoter cis-acting element annotation, and spatiotemporal expression profiling, we provide a comprehensive overview of ALOG gene distribution, structure, and expression patterns in Rosa.DiscussionOur findings provide insights into the potential involvement of Rosa ALOG genes in organogenesis and inflorescence patterning, highlighting their possible roles in the evolution of floral morphology and inflorescence complexity.